Is the requirement of integration of the bride optional in customary marriages? - Siyabonga Sibisi (De Jure, 2020)
SUMMARY Section 3(1) of the Recognition of Customary Marriages 120 of 1998 provides for the requirements for a valid customary marriage entered into after the commencement of the Act. The requirements are, the parties must be 18 years of age or above; they must consent to being married under customary law and the marriage must be negotiated and entered into or celebrated in terms of customary law. The result of entering into or celebrating a customary marriage is the bride be integrated into her new family. The question is, may the parties agree to waive the integration of the bride? This depends on whether this is a dispensable or indispensable requirement. The article forwards two school of thoughts; the first favours the view that integration of the bride is dispensable, whereas the second forwards the view that integration of the bride is indispensable. These two schools are analysed using largely case law. The article begins from the premise that integration of the bride is an indispensable requirement. This being said, it forwards the view that integration comprises many events, some of which are dispensable; one of these event is the handing over of the bride, which cannot be waived.